Case Report: Adult proximal humeral aneurysmal bone cyst: radical resection and reconstruction with osteoconductive allograft & reverse arthroplasty—Ecuador's first reported case and functional outcomes - Gamecho Arteaga, Gabriel; Hernández, Henry; Mestanza, Chrystian X.; Zurita, Jaime; Arias-Intriago, Marlon; Izquierdo-Condoy, Juan S. (Frontiers in Surgery, 2025)
IntroductionAneurysmal bone cysts (ABCs) are rare benign lesions, with adult cases being exceptionally uncommon. This report details a multidisciplinary approach for managing a proximal humeral ABC in an adult, emphasizing functional restoration.Case presentationA 36-year-old male presented with progressive pain, swelling, and restricted shoulder mobility. Imaging revealed an expansile lytic lesion with “soap-bubble” morphology. Histopathology confirmed a primary ABC. After failed conservative management, radical en bloc resection was performed, followed by single-stage reconstruction using osteoconductive allograft, reverse shoulder arthroplasty, and rotator cuff repair.ConclusionThis case demonstrates the efficacy of aggressive, single-stage reconstruction in adult ABCs, combining advanced orthopedic and oncologic principles. It advocates for molecular diagnostics to confirm primary lesions and supports hybrid graft-prosthesis strategies to optimize outcomes. The success of this approach provides a framework for managing rare, large ABCs in adults, encouraging further exploration of tailored surgical innovations in orthopedic oncology.